(Information letter) Model of microorganism’s inactivation for obtaining vaccines - Dercach, Svitlana; Martynov, Artur; Sklyar, Nadiya; Mariushenko, Anatoly; Kutsay, Nataliya; Diachenko, Valentina (Annals of Mechnikov’s Institute, 2023)
A model has been proposed for the production of immune drugs that can be used in specialized institutions of the Ministry of Health and the National Academy of Medical Sciences of Ukraine. These institutions include research institutes, departments of medical and pharmacological universities, laboratories of clinical departments, and biotechnology. The model is based on a new method of photodynamic inactivation of pathogenic bacteria, which destroys their RNA and DNA without changing the antigenic composition of cellular components. The candidate microorganisms are pathogenic bacteria that have been isolated from patients with purulent-inflammatory diseases and wounds with complications of infectious origin, including pathogens of nosocomial infections. Keywords: microorganism’s inactivation, vaccines